PENGARUH BRAND IMAGE DAN KUALITAS PELAYANAN JASA TERHADAP KEPUASAN KONSUMEN PATRA JASA SEMARANG CONVENTION HOTEL - Oki Zulfiandri Daniar; Rodhiyah Rodhiyah (Jurnal Ilmu Administrasi Bisnis, 2017)
Consumer satisfaction is the level of feeling in which a person declares the comparative results of the service performance received and expected. The convenience and service provided are different depending on the room class used, because of the difference of room class one with other rooms, this is what influences the customer's perception (value expected) with brand image of Patra Jasa Semarang Convention Hotel. All of that, will affect the level of satisfaction of each consumer. The purpose of the study to determine the effect of brand image and service quality to customer satisfaction hotel. This type of research is explanatory research, with data collection techniques through questionnaires and interviews. The population in this study is the customer Patra Jasa Semarang Convention Hotel, by using the theory of Cooper and Emory then taken 100 respondents to be sampled and the sampling technique used a combination of incidental sampling and purposive sampling. This research uses quantitative analysis technique Analytical methods used validity test, reliability test, simple linear regression analysis and multiple linear regression analysis, coefficient of determination, significance test (t test) and (f test), with SPSS tool version 16.0. The results of this study indicate that the variable brand image, service quality and customer satisfaction included in the category good, but there are still items of questions that have scores below the average. Variable brand image (X1) has an effect on consumer satisfaction (Y) equal to 37%. Service quality variable (X2) has an effect on consumer satisfaction (Y) equal to 46,9%. The conclusion of this research indicate that variable of brand image (X1) and service quality (X2) have positive effect to customer satisfaction of hotel (Y). Suggestions that can be given to Patra Jasa Semarang Convention Hotel must improve and improve service to the consumer either from improvement of hotel physical facility and also service from employee. So that consumers will feel the deeper influence of the brand image and quality of hotel services in measuring customer satisfaction.